(untitled) (MAUSAM, 1984)
The failure of southwest monsoon over the Indian sub-continent during 1979, has once’ again resulted in widespread severe drought conditions in most parts of the country. Agricultural production especially, in the dryland tracts has decreased considerably, during the year of worst drought in this decade (1971-80). In the semi-arid region of Delhi, the variations in drought parameters that led to the acute drought situation in this year have been critically examined. During the Kharif and Rabi seasons, the run off water balance components have been studied on a weekly basis with a view to understand the impact both individually and collectively on general crop growth in the region. A comparison of the water balance parameters during 1979, with those of a normal, wettest and driest years in the decade as determined from water budgeting procedure and also from cumulative water deficit diagrams has been presented and discussed.